Investigation of the genotoxicity of substances migrating from polycarbonate replacement baby bottles to identify chemicals of high concern. (March 2016) - Mertens, Birgit; Simon, Coraline; Van Bossuyt, Melissa; Onghena, Matthias; Vandermarken, Tara; Van Langenhove, Kersten; Demaegdt, Heidi; Van Hoeck, Els; Van Loco, Joris; Vandermeiren, Karin; Covaci, Adrian; Scippo, Marie-Louise; et al.
Abstract: Due to the worldwide concern that bisphenol A might act as an endocrine disruptor, alternative materials for polycarbonate (PC) have been introduced on the European market. However, PC-replacement products might also release substances of which the toxicological profile – including their genotoxic effects – has not yet been characterized. Because a thorough characterization of the genotoxic profile of all these substances is impossible in the short term, a strategy was developed in order to prioritize those substances for which additional data are urgently needed. The strategy consisted of a decision tree using hazard information related to genotoxicity. The relevant information was obtained from the database of the European Chemicals Agency (ECHA), in silico prediction tools (ToxTree and Derek Nexus TM ) and the in vitro Vitotox ® test for detecting DNA damage. By applying the decision tree, substances could be classified into different groups, each characterized by a different probability to induce genotoxic effects. Although none of the investigated substances could be unequivocally identified as genotoxic, the presence of genotoxic effects could neither be excluded for any of them. Consequently, all substances require more data to investigate the genotoxic potential. However, the type and the urge for these data differs among the substances. Highlights: Compounds with unknown toxicity migrate from polycarbonate replacement bottles. Identification of priority compounds with in silico, in vitro and literature data. None of the investigated compounds unequivocally identified as genotoxic. More data required for all compounds to further investigate the genotoxic potential. Type and urge for these data differ among the compounds.